2020
DOI: 10.1186/s12887-020-02153-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization pattern of kangaroo mother care after introduction in eight selected neonatal intensive care units in China

Abstract: Background: Kangaroo mother care (KMC) is an evidence-based and cost-effective intervention that could prevent severe complications for preterm babies, however it has not been widely adopted in China. In this study, we aim to investigate the feasibility and parental experience of adopting KMC in a Chinese context by studying the implementation of a KMC program in eight self-selected neonatal intensive care units (NICUs). Methods: A cross-sectional study of 135 preterm infants discharged from eight NICUs in Apr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…A study from the United States found that the average gestational age of infants who received KMC was around 33 weeks, with KMC being performed when the infant was in a stable condition [18]. However, another study that included infants in a NICU with a gestational age less than 32 weeks found that KMC could be initiated after several days once the infant was considered to be in stable condition by a neonatologist [19,20]. Infants with a gestational age less than 32 weeks generally have a longer stay in the NICU, leading to more anxiety among the infant's family members, which could lead to a longer period of more intense KMC education during the infant's hospitalization [19].…”
Section: Gestational Agementioning
confidence: 99%
See 3 more Smart Citations
“…A study from the United States found that the average gestational age of infants who received KMC was around 33 weeks, with KMC being performed when the infant was in a stable condition [18]. However, another study that included infants in a NICU with a gestational age less than 32 weeks found that KMC could be initiated after several days once the infant was considered to be in stable condition by a neonatologist [19,20]. Infants with a gestational age less than 32 weeks generally have a longer stay in the NICU, leading to more anxiety among the infant's family members, which could lead to a longer period of more intense KMC education during the infant's hospitalization [19].…”
Section: Gestational Agementioning
confidence: 99%
“…However, another study that included infants in a NICU with a gestational age less than 32 weeks found that KMC could be initiated after several days once the infant was considered to be in stable condition by a neonatologist [19,20]. Infants with a gestational age less than 32 weeks generally have a longer stay in the NICU, leading to more anxiety among the infant's family members, which could lead to a longer period of more intense KMC education during the infant's hospitalization [19]. This can provide an opportunity for more successful KMC for very preterm infants.…”
Section: Gestational Agementioning
confidence: 99%
See 2 more Smart Citations
“…Adequate spacing, equipment and human resources are key points to successful KMC implementation. Due to the practice of restricting parental access to NICUs in China, the KMC protocol developed was for intermittent KMC [ 8 , 9 ]. Despite the improved service capacity, we did not observe an increase in KMC coverage, which is contrary to the perspective that hospital infrastructure is the main barrier to KMC implementation.…”
mentioning
confidence: 99%